The Effect of Using the Creative Solution Model for Mathematical Problems (CPS) in Generative Thinking Skills for Second Intermediate Grade Female Students - Dr.Mudrika Salih Abdullah , Zainab Hassan Wahab (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The current study aims at identifying the effect of using the creative solution model for mathematical problems (CPS) in generative thinking skills for second intermediate grade female student. This sample consists of (65) female student from the second intermediate class, which was randomly distributed into two groups, one is experimental with (33) female students, and the other is (32). An experimental design with two equivalents was used, a test for generative thinking skills prepared consisting of )25) paragraphs, )15) including multiple choice paragraphs with four alternatives distributed on three components (hypothesis setting, prediction in light of data, identification of errors and inaccuracies) and (10) of these article paragraphs are divided into two components (fluency & flexibility). The validity of the instrument and the psychometric properties were confirmed, and stability was calculated via using the kuder-richardson equation 20, and the results were treated by using the t-test equation for two independent sample, and the results showed a statistically significant difference (0.05) between the mean scores of the two groups experimental and control in the test of generative thinking skills.